Development of a methodology to measure the effect of ergot alkaloids on forestomach motility using real-time wireless telemetry - Egert, Amanda M.; Klotz, James L.; McLeod, Kyle R.; Harmon, David L. (Frontiers in Chemistry, 2014)
The objectives of these experiments were to characterize rumen motility patterns of cattle fed once daily using a real-time wireless telemetry system, determine when to measure rumen motility with this system, and determine the effect of ruminal dosing of ergot alkaloids on rumen motility. Ruminally cannulated Holstein steers (n = 8) were fed a basal diet of alfalfa cubes once daily. Rumen motility was measured by monitoring real-time pressure changes within the rumen using wireless telemetry and pressure transducers. Experiment 1 consisted of three 24-h rumen pressure collections beginning immediately after feeding. Data were recorded, stored, and analyzed using iox2 software and the rhythmic analyzer. All motility variables differed (P < 0.01) between hours and thirds (8-h periods) of the day. There were no differences between days for most variables. The variance of the second 8-h period of the day was less than (P < 0.01) the first for area and less than the third for amplitude, frequency, duration, and area (P < 0.05). These data demonstrated that the second 8-h period of the day was the least variable for many measures of motility and would provide the best opportunity for testing differences in motility due to treatments. In Exp. 2, the steers (n = 8) were pair-fed the basal diet of Exp. 1 and dosed with endophyte-free (E-) or endophyte-infected (E+; 0 or 10 μg ergovaline + ergovalinine / kg BW; respectively) tall fescue seed before feeding for 15 d. Rumen motility was measured for 8 h beginning 8 h after feeding for the first 14 d of seed dosing. Blood samples were taken on d 1, 7, and 15, and rumen content samples were taken on d 15. Baseline (P = 0.06) and peak (P = 0.04) pressure were lower for E+ steers. Water intake tended (P = 0.10) to be less for E+ steers the first 8 hour period after feeding. The E+ seed treatment at this dosage under thermoneutral conditions did not significantly affect rumen motility, ruminal fill, or dry matter of rumen contents.